Tumor necrosis factor receptor superfamily in T cell priming and effector function - Muller, J; Baeyens, A; Dustin, ML (Elsevier, 2018)
The tumor necrosis factor receptor superfamily (TNFRSF) and their ligands mediate lymphoid tissue development and homeostasis in addition to key aspects of innate and adaptive immune responses. T cells of the adaptive immune system express a number of TNFRSF members that are used to receive signals at different instructive stages and produce several tumor necrosis factor superfamily (TNFSF) members as effector molecules. There is also one example of a TNFRSF member serving as a ligand for negative regulatory checkpoint receptors. In most cases, the ligands in afferent and efferent phases are membrane proteins and thus the interaction with TNFRSF members must take place in immunological synapses and other modes of cell–cell interaction. A particular feature of the TNFRSF-mediated signaling is the prominent use of linear ubiquitin chains as scaffolds for signaling complexes that activate nuclear factor κ-B and Fos/Jun transcriptional regulators. This review will focus on the signaling mechanisms triggered by TNFRSF members in their role as costimulators of early and late phases of T cell instruction and the delivery mechanism of TNFSF members through the immunological synapses of helper and cytotoxic effector cells.